NOUN FORMATION IN PAKPAK LANGUAGE - Cinta Laswarna Berutu; Zainuddin (State University of Medan, 2015)
This study deals with Noun Formation in Pakpak Language. The objectives of thisstudy are to find and describe the noun formation in Pakpak language. Themethod of this research is library research by reading some books related to thisstudy, this research was conducted by descriptive qualitative research method.The data of this research are taken from two sources, namely: from Folklorewritten in Pakpak language and from short story written in Pakpak language. Thetechnique of analyzing data is documentary technique, the researcher usedHockett and Robin theory which is developed by Kridalaksana to analyze the dataand found that there are four types of affixation used in folklore and short storywritten in Pakpak language. The four types of affixation are: (1). prefix (19, 19%),(2). infix (10, 10%), (3). suffix (36, 36%), (4). confix (34, 34%). Noun formationin Pakpak language not only caused by attached an affix but also by reduplicationprocess, the researcher found that there are five types of reduplication used infolklore and short story in Pakpak language, they are: reduplication of a wholebasic form, reduplication which is basically just repeating the root, reduplicationwhich is change the phoneme (phoneme variation), reduplication through theprocess of adding affixes and compound reduplication. The researcher also foundthe rules of morphophonemic used in Pakpak language, phonological assimilationand phonological addition. As the result, there are four types of affixation informing noun in Pakpak language.